Peran Orangtua Terhadap Motivasi Belajar Anak - Liana Nur Fadillah; Bahrun Ali Murtopo; Nadia Raifah Nawa Kartika (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to analyze the contribution of farmer parents, traders, and elderly parents inproviding children's learning motivation and the factors that inhibit and support farmer parents,traders, and elderly parents in motivating children to learn in Kalisari Village, RowokeleDistrict, Kebumen Regency. This study uses a descriptive qualitative approach by emphasizingprimary and secondary data sources. The subjects of this study were parents and children. Datacollection techniques in this study used observation techniques, interviews, and documentationwhile data analysis techniques namely, data reduction, data presentation and verification. Theresults of the study found that the role of parents in children's learning motivation in KalisariVillage, Rowokele District, Kebumen Regency was in a fairly good category. Parents try togive encouragement to their children and always increase children's learning motivation,namely by providing children's learning facilities, supervising children's learning activities athome during free time or at night. Even though there are several obstacles such as busy workso that in supervising and accompanying children to study becomes less, these obstacles can beovercome so that the role of parents in accompanying children to study and the children's ownlearning activities is carried out and children's motivation increases, and children can achieveachievements according to the desired goals either by the children themselves or the parents